Conductivity of nanoporous InP membranes investigated using terahertz spectroscopy - Merchant, S; Lloyd-Hughes, J; Sirbu, L; Tiginyanu, I; Parkinson, P; Herz, L; Johnston, M; IEEE (2007)
We have investigated the conductivity of equilibrium and photoexcited electrons in nanoporous Indium phosphide (InP) of various porosities and of two orientations: (100) and (111). We observed an enhanced transmission through the nanoporous samples compared with bulk InP, resulting from a suppression of the conductivity by the pores. The frequency-dependent conductivity was extracted numerically from the transmission data. We examined the dynamical conductivity of photoexcited carriers using optical-pump THz-probe spectroscopy. After the rapid photoexcitation of electrons, the time-resolved conductivity was observed to decay slowly, with carrier recombination lifetimes exceeding 1ns for all (100)- and (111)-oriented samples.